(untitled) (Fiep Bulletin - online, 2012)
The aim of this study was to evaluate the cold pain threshold front therapy with transcutaneous electrical nerve stimulation (TENS) in healthy subjects, using a bipolar application technique on the nerve root. The study included 18 volunteers of both sexes, who underwent two treatments, with a current TENS and a placebo, and moments induced hypothermia in order to provoke a painful response. Subjects were evaluated by using VAS and latency of cold pain. As a form of electrical stimulation, TENS used the burst mode, and individuals were evaluated at three time points: immediately after, 20 minutes and one hour after electrostimulation. As to results, the data obtained through the EVA show a significant increase in pain threshold for individuals undergoing therapy with TENS in evaluations after 20 minutes and an hour compared to the pre assessment and intervention immediately after. For evaluation of the pain threshold to cold by the time, there were no significant differences in the comparisons. They found that as the application of burst TENS is effective in increasing the pain threshold stimulation promoted by low temperature.